If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7 + -7 = -6 + 6x Reorder the terms: -7 + -7 + 5x = -6 + 6x Combine like terms: -7 + -7 = -14 -14 + 5x = -6 + 6x Solving -14 + 5x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -14 + 5x + -6x = -6 + 6x + -6x Combine like terms: 5x + -6x = -1x -14 + -1x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 -14 + -1x = -6 + 0 -14 + -1x = -6 Add '14' to each side of the equation. -14 + 14 + -1x = -6 + 14 Combine like terms: -14 + 14 = 0 0 + -1x = -6 + 14 -1x = -6 + 14 Combine like terms: -6 + 14 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| 3(x+4)+4x=-2 | | X^2+.8x+c=0 | | x+1/5=2x-1/6 | | 0.9x^2-10x+22=0 | | -8+(-5a)= | | 6.5*x=756 | | X^2+11x+c=0 | | x+4=(-2)-8 | | 1-4b=13-3b-3b | | 4m-16=-30 | | (2x^2-3x-2)-(x^2+9)=x^2+14 | | 14x+14=98 | | 49/42=7/x | | 2(4x+1)(3x-2)=0 | | 4x-2(3x+1)=10 | | X^2-0.36x+c=0 | | -4b+21=-4b | | 4(-6x+1)-5x=91 | | 4m-16=-3 | | (y-4)2-7(2-y)=(y+5)(y-2) | | X^2-2.2x+c=0 | | -9y-40=36y-14 | | 4(x-3)+4(x+1)=11-2x | | 9+8z-3+5z= | | 2+w=90 | | 2x=11-5y | | 3(n+5)+2=21 | | 2x-16=5(x+1) | | (7x^2+5x-3)-(7x^2+5)=27 | | 2w+w=90 | | .25x=-.001 | | N+(-36)=36 |